Farm Mechanization : A New Challenge for Agriculture in Low and Middle Income Countries of Europe and Central Asia - World Bank (Washington, DC, 2013)
This report shows that trends in farm mechanization are attributable to differing approaches to reform and differing agricultural resource endowments. The level of reform determines the pattern and extent to which labor and capital change, with land reform and commodity market liberalization as the underlying forces for change. These reforms substantially raise the incentives to invest as a means to increase productivity and incomes. In countries where this initial threshold of reform has not been attained agricultural incomes grow more slowly and there is less incentive to invest. Where the incentives to invest are high a second round of reform is necessary to facilitate investment reforms which deepen and strengthen financial markets and improve the business environment.